Profesioanalitas Aparatur dalam Penyelenggaraan Pelayanan Publik di Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu Kota Gorontalo - Nur Padillah Sahibuddin; Arifin Tahir; Sri Yulianty Mozin (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
This study aims to determine and analyze the Professionalism of Apparatus in the Implementation of Public Services at the Investment and One-Stop Integrated Services Office of Gorontalo City. Viewed from the aspects of: (1) Competence, (2) Effectiveness, (3) Efficiency, and (4) Responsibility. This research method uses a Qualitative Approach with a Descriptive type. Data collection techniques used in this study are observation, interviews, and documentation. The results of the study indicate that in the competence dimension, the apparatus has had adequate technical capabilities, evidenced by mastery of the OSS system and participation in various training. The effectiveness dimension is also quite good, indicated by the timeliness of service even though sometimes hampered by OSS network disruptions. In the efficiency dimension, services have run optimally through the use of online systems that save time and costs, and received support from the SKM results with a value of 90.17 in the "very good" category. Meanwhile, in the responsibility dimension, the apparatus shows high discipline and work commitment, although there are still several cases of delays and permission to leave the office during working hours. Overall, it can be concluded that the professionalism of the Gorontalo City DPMPTSP apparatus in providing public services is classified as good, but still requires improvement, especially in the aspects of effectiveness and responsibility.